Hydrodynamic characterisation of chitosan and its interaction with two polyanions: DNA and xanthan. (20th May 2015) - Almutairi, Fahad M.; Erten, Tayyibe; Adams, Gary G.; Hayes, Maria; McLoughlin, Pádraig; Kök, M. Şamil; Mackie, Alan R.; Rowe, Arthur J.; Harding, Stephen E.
Highlights: Hydrodynamics of chitosans of different mol.wt and degree of acetylation compared. Combination of modern analytical ultracentrifugation with other methods. Principle of co-sedimentation used to monitor interactions with xanthan & DNA. Interactions showed a strong dependence on mol.wt. Relevance of this for DNA condensation considered. Abstract: Chitosan, a soluble polycationic derivative of insoluble chitin, has been widely considered for use in the food, cosmetic and pharmaceutical industries. Commercial ("C") and in-house laboratory ("L") prepared chitosan samples extracted from crustaceous shells with different molecular weight and degrees of acetylation (25% and 15%) were compared with regards to (i) weight–average molecular weight ( M w ); (ii) sedimentation coefficient ( s o 20, w ) distribution, and (iii) intrinsic viscosity ([ η ]). These parameters were estimated using a combination of analytical ultracentrifugation (AUC), size exclusion chromatography coupled to multi-angle laser light scattering (SEC–MALS) and differential pressure viscometry. Polydisperse distributions were seen from sedimentation coefficient distributions and elution profiles from SEC–MALS. M w values obtained for each sample by sedimentation equilibrium measurements were in excellent agreement with those obtained from SEC–MALS. Mark–Houwink–Kuhn–Sakurada (MHKS) and Wales van Holde analyses of the data all suggest a semi-flexible conformation. The principle of co-sedimentation was then used to monitor the interactions of the two different molecular weights of L chitosans with two polyanions, DNA and xanthan (another double helical high molecular weight molecule). Interactions were clearly observed and then quantified from the changes in the sedimentation coefficient distribution of the mixture compared to unmixed controls using sedimentation velocity. The interactions appeared to show a strong dependence on molecular weight. The relevance of this for DNA condensation applications is indicated.